2021
DOI: 10.3390/rs13091719
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Diurnal Changing Patterns in Airborne Crop Remote Sensing Images

Abstract: Airborne remote sensing technologies have been widely applied in field crop phenotyping. However, the quality of current remote sensing data suffers from significant diurnal variances. The severity of the diurnal issue has been reported in various plant phenotyping studies over the last four decades, but there are limited studies on the modeling of the diurnal changing patterns that allow people to precisely predict the level of diurnal impacts. In order to comprehensively investigate the diurnal variability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…We have built calibration models for the other sources of variability. Two examples can be found in the published papers [ 33 , 34 ]. In this paper, we are focused on only calibrating the slope factor, and hopefully by combining this with the other previous models, we will keep improving the remote sensing quality.…”
Section: Resultsmentioning
confidence: 99%
“…We have built calibration models for the other sources of variability. Two examples can be found in the published papers [ 33 , 34 ]. In this paper, we are focused on only calibrating the slope factor, and hopefully by combining this with the other previous models, we will keep improving the remote sensing quality.…”
Section: Resultsmentioning
confidence: 99%
“…[48] established that the RF algorithm was best for estimating maize's specific leaf area, equivalent water thickness, and fuel moisture content to rRMSEs of 3.48%, 3.13%, and 1%, respectively. RF has been applied to predict the CWSI for crops other than maize [49][50][51]. For instance, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[50] observed that RF outperformed SVM in estimating chlorophyll content, with average RMSEs of 2.90 and 3.11, respectively. However, SVM has also shown promising results in predicting relative water content, achieving an R 2 of 0.72 and an RMSE of 6.22% [49]. Nonetheless, the literature also shows that, despite the optimum performance of these machine learning algorithms, no algorithm has been exhaustively tested to enable the accurate and effective identification and mapping of plant characteristics in a variety of environments [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the time of the day and the location of the field, the sunlight intensity and angle can change drastically [ 27 ]. The normalized difference vegetation index (NDVI) of the plant follows a V-shaped pattern where the minimum is at solar noon time when the sun is at the highest location in the sky [ 28 ]. Additionally, a field hyperspectral camera can only achieve a 10 mm spatial resolution after orthorectification [ 29 ].…”
Section: Introductionmentioning
confidence: 99%